Developing sustainability in the Italian meat supply chain: an empirical investigation. Issue 4 (16th February 2017) - Golini, Ruggero; Moretto, Antonella; Caniato, Federico; Caridi, Maria; Kalchschmidt, Matteo
Abstract : Although sustainable supply chain (SC) management has been widely investigated in recent years, the focus has mainly been on the practices adopted by a single company, so missing the big picture at SC level. This study of the Italian meat industry considers the SC as a whole, identifying the critical points for each stage in terms of economic, environmental and social sustainability. To this end, a first set of case studies was conducted of companies at different stages of the SC before turning to focus on the meat processing stage, which was identified as critical and highly relevant. A second set of case studies analysed how these companies leverage SC management practices to develop sustainable SCs. In so doing, specific attention was paid to drivers and contingent variables that foster the adoption of sustainable practices. The results of the two steps were then merged to illuminate how practices adopted by the meat processors can impact on the whole chain, confirming their pivotal role in driving sustainability. These results provide a holistic view of the phenomenon, encompassing the entire chain from end to end and highlighting the interdependences across various stages of the meat SC.